"…That which we call a rose…": A critical analysis of rapid on‐site evaluation. Issue 12 (11th November 2016) - Zakowski, Maureen F.
Abstract : Rapid on‐site evaluation (ROSE) is a term used in cytology. A PubMed search demonstrates a plethora of articles regarding ROSE, much of it outside the cytology literature and written without the input of cytologists. The purpose of this commentary is to provide an overview of the current state of the literature regarding this component of cytology practice and to introduce a few suggestions that may aid in the evaluation of the usefulness of ROSE.